Registry of Senior Australians (ROSA): integrating cross-sectoral information to evaluate quality and safety of care provided to older people. Issue 11 (17th November 2022) - Inacio, Maria C; Caughey, Gillian Elizabeth; Wesselingh, Steve
Abstract : Purpose: The Registry of Senior Australians (ROSA) was established to evaluate aged care experiences in Australia. In this manuscript, we describe the ROSA framework, the two ROSA cohorts, highlights from research findings, and future plans. Participants: The South Australian ROSA Prospective Cohort (August 2018–June 2020) enrolled 26 605 participants, of which 59.2% (N=15 745) are women, with a median age of 83 (interquartile range (IQR) 77–88). The National ROSA Historical Cohort (January 2002–June 2020) includes 1 694 206 participants with an aged care eligibility assessment, of which 59.1% (N=1 001 705) are women and the median age is 78 (IQR 72–83). Findings to date: Most research using the ROSA has focused on dementia, service accessibility, quality and safety of care, falls and injuries and quality use of medicines. The ROSA has also examined the experience of individuals with highly prevalent and understudied conditions in aged care settings (eg, eye and mental health) and aspects of services (eg, built environment) and innovation (eg, mobile radiological services) that can affect older people's health. Important learnings from the ROSA's development include the significant resources and multidisciplinary expertise required for establishing this platform. Between 2018 and 2022, 43 academic publications, eight reports of the Australian Government Royal Commission into Aged Care Quality and Safety, and several reports to state health authorities and professional societies have used the ROSA. Future plans: Our plans include to: (1) continue delivering high-quality evidence to support the improvement of ageing and aged care services; (2) influence and improve the quality of research in and for the aged care sector; (3) expand scope to facilitate examining aims in more depth; (4) include future aged care sector data collections within the ROSA; (5) inform best practices and innovate how consumer engagement occurs in research; (6) monitor and evaluate the impact of the 2021 Australian Aged Care Reforms.